(untitled) (Journal of National Institute of Ophthalmology, 2025)
Objective: To assess efficacy of brimonidine 0.2% in the control of per-operative bleeding in pterygium surgery. Methodology: This quasi-experimental study was conducted was in the department of Cornea, National Institute of Ophthalmology from January, 2019 to December, 2020 on 196 diagnosed patients of primary progressive pterygium. They were grouped into group-A (experimental group-brimonidine 0.2% used as per-operative bleeding control agent) and group-B (control group- only pressure was applied to control per-operative bleeding). Patients were selected based on specific selection criteria. Selected patients underwent detail ocular and systemic evaluation as well as relevant investigations. Excision of pterygium with conjunctival limbal autograft was done in all patients by a single competent surgeon. In patients of group A, topical brimonidine 0.2% were applied 3 times prior to surgery (15 minutes, 10 minutes and 5 minutes prior to surgery). Per-operative bleeding was quantified by counting the number of micro-sponges (weck cel) used. Grading of haemorrhage was done based on number of microsponge used during surgery and grouped into Grade-I, where 1-3 microsponge used per-operatively to control bleeding, grade-II where 4-6 microsponge used per-operatively to control bleeding and Grade-III, where 1-3 microsponge used per-operatively to control bleeding. Results: Mean age of patients were 40.6±10.2 (SD) years in group-A and 39.8±13.22 (SD) years in group-B respectively. Out of 98 patients in group A, 61.2% were male and 38.8% were female and in group B, 63.3% were male and 36.7% were female. In group-A, 60(61.3%) patients belong to grade-I, 22(22.4%) patients belong to grade-II, 16(16.3) patients belong to grade-III. In group-B, 28(28.6%) patients belong to grade-I, 34(34.7%) patients belong to grade-II, 36(36.7%) patients belong to grade-III. In group-A and B, mean operation time were 15.5±0.99 (SD) min. and 22.3±1.77 (SD) minutes respectively( p value <0.001). In group-A, the mean pre-operative value of IOP was 15.04±1.46 (SD) mm of Hg and at the end of surgery, 13.6±2.02 (SD) mm of Hg (p value >0.06). In group-B, the mean pre- operative value of IOP was14.94±1.81 mm of Hg and at the end of surgery, 14.6±1.62 (SD) mm of Hg (p value >0.076). Conclusion: Analysis of the study findings shows that topical brimonidine 0.2% significantly reduces per-operative bleeding in pterygium surgery without affecting IOP. J.Natl.Inst.Ophthalmol. 2023; 6(2):10-16